The Prevalent Cases of Endometrial Carcinoma in Different Life Periods of Women – Clinical and Histopathological Diagnosis - Hajrullah LATIFI; Astrit M. GASHI; Drilon LATIFI (Modern Medicine)
Abnormal uterine bleeding is a term used to describe any irregular bleeding from the uterus that is not part of a woman’s normal menstrual cycle and can happen during different life periods. Abnormal uterine bleeding can have structural etiologies (polyp, adenomyosis, leiomyoma, malignancy) or nonstructural etiologies (coagulopathy, ovulatory dysfunction, and not-classified). The post- and pre-menopausal period requires a detailed investigation to establish the etiology of the bleeding because the chances that the woman has a malignancy are plentiful in this period. The treatment plan is determined based on the underlying cause of the bleeding. The main objective of this paper was to determine the prevalence of endometrial carcinoma in different periods, focusing on the postmenopausal period. This research was a cross-sectional study and included 79 cases of abnormal uterine bleeding in different periods of women’s lives. Our study found that abnormal uterine bleeding occurs more frequently during the premenopausal period (59%) and that the causes of irregular bleeding during this period were mainly benign. Our study focused on the postmenopausal period, where we found that 32.9% of irregular uterine bleeding occurs during this period, and the leading causes were malignant pathologies (83.3%), mainly endometrial adenocarcinomas. The average age was 66.7 years. During the study, it was observed that 50% of women with abnormal uterine bleeding due to malignancy were classified as overweight, 25% were obese, and 25% had normal weight. It was confirmed that obesity is a co-factor of malignancy in the postmenopausal period, and the pathophysiological mechanism is well understood now. Our study also found a high number of co-morbidities among women with abnormal uterine bleeding due to malignancy. We came to the conclusion that any abnormal uterine bleeding should be initially investigated in a multidisciplinary manner, an accurate diagnosis should be determined, and then a treatment plan should be established. The treatment strategy should be determined depending on the cause of abnormal bleeding.